Collaborative ethnography in a border context with migrant children: theoretical-methodological reflections. (Polis (Santiago), 2025)
This article presents a theoretical-methodological reflection based on the experience of collaborative ethnographic fieldwork with irregular migrant girls and boys in the border region of Tarapacá, Chile, between the years 2023 and 2024. It introduces the concept of "child participatory mandate" to question the automatic application of ideals proposed by international organizations, promoting a critical reflection on child participation in social studies of childhood. It highlights collaborative ethnography as a respectful methodology that facilitates the co-construction of knowledge among girls and boys in border contexts. The main contributions of this paper include the innovative use of workshops and visual techniques to delve into the complex experiences of migrant childhoods, criticizing conventional norms of citizenship and rights.